Conceptions of undergraduate students about the teaching and learning processes in different lifecycles (Research, Society and Development, 2018)
Educational Psychology has been present as an academic discipline in the various undergraduate courses. Considering the importance of this area for the training of teachers, this work aims to analyze the conceptions of UFRN’s undergraduate students about the teaching and learning processes on the infancy, adolescence, youth and adult life. Mixed methods were used, with data gathering through semi-structured questionnaires applied with a sample of 319 students, of which 152 did not attend components of Educational Psychology and 167 already attended. The data were analyzed through the Content Analysis method, subsidizing the construction of later categories, referring to the teaching and learning process, and life cycles. The results show that 44.1% of the students who did not attend and 33.5% of those who already attended components of Educational Psychology expressed conceptions of teaching and learning processes centered on the teacher; while 48.9% of those who did not attend and 48.5% of those who attended did express incoherent conceptions among themselves. Regarding the life cycles, 53.7% of the students who did not attend and 64.1% of those who attended did not differentiate the cycles; while 42.2% of students who did not attend and 34% of those who attended them differed based on stereotypes. In this way, this study contacts that it is necessary to reflect about the real contributions of the Educational Psychology and rethink its role both in the formation and in the teaching performance.